New magnetogels based on manganese ferrite nanoparticles and self-assembled peptide hydrogels as drug nanocarriers - Veloso, Sérgio R. S. (2017)
In this work, superparamagnetic manganese ferrite (MnFe2O4) nanoparticles were successfully incorporated in self-assembled peptide-derived hydrogels. The new magnetogels were tested as nanocarriers for two fluorescent drugs, curcumin (an anticancer and neuroprotective drug) and a new antitumor thienopyridine derivative. Fluorescence-based techniques (fluorescence emission, FRET and fluorescence anisotropy) were used to assess incorporation of these drugs in the magnetogels and their transport towards models of biological membranes. It can be observed that the drug moves to the model membranes upon interaction of the drug-loaded magnetogels with membranes.